FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENABUNG DI BANK ACEH (STUDI KASUS MASYARAKAT KABUPATEN GAYO LUES) - Fatimah; Muhammad Ikhwan; Safwan Kamal (JIM: Jurnal Ilmiah Mahasiswa, 2020)
The main problem in this research is how the influence of knowledge, promotion, and location factors on the community's interest in saving at Bank Aceh. The purpose of this study is to determine how these factors have a partial and simultaneous influence on people's interest in saving at Bank Aceh. The data obtained came from respondents, namely Blangkejeren and Pining sub-districts, Gayo Lues district, the technique used was purposive sampling of 100 people, the research method was a quantitative method by surveying and distributing questionnaires as data collection techniques. The analytical tool used is the classical assumption method using multiple linear regression analysis, t test or partial test, F test or simultaneous test and coefficient of determination. The results of this study indicate that based on the F test the knowledge, promotion and location factors have a positive and significant effect on people's interest in saving at Bank Aceh. And based on the t-test, knowledge, promotion and location factors have a significant positive effect on people's interest in saving, this is because the Sharia Bank is in an easily accessible location and makes it easy for the public to make transactions at Bank Aceh, good promotions conducted by Bank Aceh can attract interest people save at Bank Aceh as well as public knowledge that makes the community's interest to save more at Bank Aceh.